KAJIAN PENERAPAN PERSYARATAN KENYAMANAN KONDISI RUANG, PANDANGAN, TINGKAT KEBISINGAN DAN TINGKAT GETARAN PADA BANGUNAN GEDUNG - Hurip Hidayat (FTSP Universitas Jayabaya, 2022)
This study intends to find representative problems in the application of requirements for comfort, spatial conditions, views, noise levels and vibration levels in buildings referring to Government Regulation Number 36 of 2005 concerning Regulations for Implementing Law Number 28 of 2002 concerning Buildings. Data obtained from observations and measurements of research objects in the form of four buildings with different functions and locations compared to related standards resulted in several problems, including: the room felt hot, the building was damaged due to increased humidity in the building, the room felt cramped, disturbing privacy, disturbing view, glare effect, visual disturbance, disturbing conversation and quietness in space, and noise in space. in particular and the reliability of the building.